The Stock Market and the Productivity Slowdown: International Evidence - Kaufman, Roger T.; Jacoby, Richard A. (The Review of Economics and Statistics, 1986)
Extending Baily's model of the productivity slowdown to the manufacturing sectors of five other countries, we find that a decline in the growth of capital services, reflected in declines in the stock market, can explain much of the 1973-1978 decline in productivity abroad as well as in the United States. We also show, however, that the stock market declines often preceded the declines in productivity growth, and the model is less successful when the sample period is extended through 1981.